2016
DOI: 10.3164/jcbn.15-140
|View full text |Cite
|
Sign up to set email alerts
|

Disorder of autonomic nervous system and its vulnerability to external stimulation in functional dyspepsia

Abstract: To elucidate the role of autonomic nervous system in functional dyspepsia patients, we examined 24-h heart rate variability: the basal levels, responses after lunch, cold pressor and mental arithmetic tests, and the efficacy of an autonomic drug (tofisopam). The high-frequency component (HF: 0.15–0.40 Hz) and the ratio of HF to the low-frequency component (LF: 0.04–0.15 Hz; LF/HF ratio) were used as indicators of parasympathetic and sympathetic autonomic nervous system function. The HF component in the 24-h, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…( 4 – 6 ) Furthermore, the involvement of several other mechanisms has also been suggested, including duodenal hypersensitivity to the luminal contents, small bowel dysmotility, Helicobacter pylori ( H. pylori ) infection, ( 7 ) psychological disturbances ( 8 ) and central nervous system disorders. ( 9 , 10 ) Since FD patients, especially epigastric pain syndrome (EPS) patients, can be classified into heterogenic subgroups, the use of proton pump inhibitors in the treatment of EPS is controversial. ( 11 15 ) Previous study has reported an association between FD and pancreatic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…( 4 – 6 ) Furthermore, the involvement of several other mechanisms has also been suggested, including duodenal hypersensitivity to the luminal contents, small bowel dysmotility, Helicobacter pylori ( H. pylori ) infection, ( 7 ) psychological disturbances ( 8 ) and central nervous system disorders. ( 9 , 10 ) Since FD patients, especially epigastric pain syndrome (EPS) patients, can be classified into heterogenic subgroups, the use of proton pump inhibitors in the treatment of EPS is controversial. ( 11 15 ) Previous study has reported an association between FD and pancreatic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Among various types of stress, childhood trauma such as sexual or physical abuse is significantly associated with abdominal symptoms via HPA axis activation in humans, particularly in adult FD patients [10][11][12][13][14][15]. In addition, imbalance in the ANS, namely increased sympathetic activity and decreased vagal activity, is associated with FD pathogenesis including dyspeptic symptoms [31,32]. Therefore, the present findings of histological changes in gastric EGC processes upon maternal separation (a well-established experimental model of early-life stress) may be in part a microscopic indicator of FD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…FD has been described as a multifactorial disease that involves the ENS and the CNS (Sahan et al 2018). It has been reported that FD patients manifest an imbalance of ANS function and vulnerability to recovery from external stimuli (Tominaga et al 2016). Automatic dysfunction, including that of the sympathetic and parasympathetic system, has been observed in patients with FD (Park et al 2001).…”
Section: Introductionmentioning
confidence: 99%